Analysis of Rebranding the X Application on User Loyalty in Batam City - Suwarno Suwarno; Mangapul Siahaan; Annisya Putri Nadhia (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The global market is currently experiencing very fierce competition. Companies compete to implement all marketing strategies to be superior in surviving this competition, one of which is a rebranding strategy by changing the brand image of the X application which was formerly known as Twitter. This study aims to determine whether the effect of rebranding can affect the loyalty of X’s users by assessing brand trust, brand prestige, and brand love. This research method uses a mixed method which is divided into two approaches, namely quantitative and qualitative using linear regression analysis. The results show brand image does not have a big influence on brand trust, brand prestige, and brand love. Furthermore, brand trust, brand prestige, and brand love have a positive influence on brand loyalty meaning that users are not too affected by the rebranding of X, but they will remain loyal to using the application.